2022
DOI: 10.5194/essd-2022-411
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A global Lagrangian eddy dataset based on satellite altimetry

Abstract: Abstract. The methods used to identify coherent ocean eddies are either Eulerian or Lagrangian in nature, and nearly all existing eddy dataset are based on the Eulerian method. In this study, millions of Lagrangian particles are advected by satellite-derived surface geostrophic velocities over the period of 1993–2019. Using the method of Lagrangian-averaged vorticity deviation (LAVD), we present a global Lagrangian eddy dataset (GLED v1.0, Liu and Abernathey, 2022, https://doi.org/10.5281/zenodo.7349753). This… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Thus, it is anticipated that these algorithms can be leveraged to compute CNOPs for more realistic models, paving the way for further exploration of paired eddies sensitivity in future studies. Furthermore, recent works have noted the significance of filamentary structures at the periphery of eddies in material transport (Liu & Abernathey, 2023; Liu et al., 2019). The findings of this study may hold important value for predicting material transport caused by eddies, presenting an interesting avenue for further research.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Thus, it is anticipated that these algorithms can be leveraged to compute CNOPs for more realistic models, paving the way for further exploration of paired eddies sensitivity in future studies. Furthermore, recent works have noted the significance of filamentary structures at the periphery of eddies in material transport (Liu & Abernathey, 2023; Liu et al., 2019). The findings of this study may hold important value for predicting material transport caused by eddies, presenting an interesting avenue for further research.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Besides the direct applications for interpreting biogeochemical responses, there are several open questions that a Lagrangian coherent eddy atlas would address. Previous studies found that fewer and smaller structures maintain coherency for longer timescales (Abernathey and Haller, 2018;Xia et al, 2022b;Liu and Abernathey, 2023). However, the average lifespan of a coherent structure is unknown.…”
Section: Lagrangian Coherency Detection From Satellite Altimetrymentioning
confidence: 99%
“…Here we define Lagrangian eddies (or RCLVs) using the LAVD method owing to its objectivity, computational efficiency, and mathematical foundation describing material rotation. RCLVs are ubiquitous in satellite altimetry observations (Abernathey and Haller, 2018;Tian et al, 2022;Xia et al, 2022b;Liu and Abernathey, 2023), and their trapping properties have been validated with in situ trajectories of Argo floats (Liu and Abernathey, 2023) and drifters (Encinas-Bartos et al, 2022).…”
Section: Lagrangian Coherency Detection From Satellite Altimetrymentioning
confidence: 99%
See 2 more Smart Citations